Disappearing Earth - Phillips, Julia (Alfred A. Knopf, 2019)
The shattering disappearance of two young girls from Russia's Kamchatka Peninsula compounds the isolation and fears of a tight-woven community, connecting the lives of neighbors, witnesses, family members, and a detective throughout an ensuing year of tension.